(untitled) (Analysis in Theory and Applications, 2016)
In this paper, we give some creative characterizations of Campanato spaces via the boundedness of commutators associated with the Calderόn-Zygmund singular integral operator, fractional integrals and Hardy type operators. Furthermore, we put forward a few problems on the characterizations of Campanato type spaces via the boundedness of commutators.